The Extra Virgin Olive Oil phenolic compounds () oleacein and () oleocanthal inhibit tumor cell autophagy - Marrero Capitán, Ana Dácil; Posligua-García, Joel; Bernal, Manuel; Ortega Vidal, Juan; Salido, Sofía; Altarejos, Joaquín; Rodríguez-Quesada, Ana María; Martínez-Póveda, Beatriz Amparo; Medina-Torres, Miguel Ángel (My University, 2023)
Our group has recently shown that the antitumor Extra Virgin Olive Oil phenolic compounds (—)oleocanthal and (—)oleacein also behave as antiangiogenic agents. Interestingly, it has been described that phenolic compounds found in the Mediterranean diet affect the autophagy pathway. Based on this background, we studied the modulatory effects of (—)oleocanthal and (—)oleacein on tumor cell autophagy. Methodologically, the tumor cell lines MDAMB231, MCF7 and HT1080 cell lines were used in in vitro cellular and molecular studies of the autophagy flux and key mediators of this process, and High Content Screening (HCS) System using Perkin Elmer Operetta for single-cell analysis was performed in these cells. Interestingly, (—)oleocanthal and (—)oleacein repressed the autophagy flux of MDAMB231 and MCF7 submitted to autophagy inducing conditions (severe starving) at doses in the low micromolar range. In addition, key autophagy mediators, like LC3 or WIPI2 proteins, were dramatically reduced in the same settings, as seen in immunohistochemical studies. Furthermore, preliminary results of HCS in tumor cells revealed depletory effects on autophagy by using specifics dyes for this process at the single-cell level. Altogether, our results point to a drastic inhibitory effect of (—)oleocanthal and (—)oleacein on tumor cell autophagy at low doses.
Es una comunicación a congreso internacional en formato póster.
Keywords: Antiangiogénicos; Fenoles - Uso terapéutico; Aceite de oliva - Uso terapéutico; Extra virgin olive oil; Oleacin; Oleocanthal; Autophagy